Pengaruh Pendidikan Agama Islam terhadap Pembentukan Karakter Siswa di Era Digital - Anggun Syahriani Putri; Rizka Harfiani (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This study aims to analyze the role of Islamic Religious Education (IRE) in shaping students’ character in the digital era, particularly through the use of non-digital learning media. The rapid development of technology has brought both positive and negative impacts on students. On one hand, technology facilitates access to information and enables more interactive learning processes. On the other hand, exposure to negative content and digital distractions can weaken students’ concentration and moral control. This research employed a quantitative method with a survey approach and a correlational design. Data were collected using a Likert-scale questionnaire from five respondents selected through purposive sampling. The findings reveal that teaching IRE using non-digital media significantly improves students’ concentration, discipline, and awareness of worship. Furthermore, IRE positively contributes to fostering wise internet usage and proper digital communication ethics. These results indicate that combining traditional approaches with the integration of religious values is highly effective in addressing the challenges of the digital era and promoting the development of students’ character rooted in Islamic values.